CD13hi Neutrophil-like myeloid-derived suppressor cells exert immune suppression through Arginase 1 expression in pancreatic ductal adenocarcinoma. (1st February 2017) - Zhang, Jing; Xu, Xiongfei; Shi, Min; Chen, Ying; Yu, Danghui; Zhao, Chenyan; Gu, Yan; Yang, Biao; Guo, Shiwei; Ding, Guiling; Jin, Gang; Wu, Chin-Lee; et al.
ABSTRACT: Perineural invasion and immunosuppressive tumor microenvironment are the distinct features of pancreatic ductal adenocarcinoma (PDAC). Heterogeneous myeloid-derived suppressor cells (MDSCs) are potent suppressors of antitumor immunity, posing obstacles for cancer immunotherapy. Increasing evidences have demonstrated the accumulation of MDSCs in PDAC patients. However, the role of MDSCs in perineural invasion of PDAC and the existence of novel MDSC subsets during PDAC remain unclear. This study found that lymphocytic perineural cuffs were frequently present in chronic pancreatitis (CP) tissues and adjacent non-neoplastic pancreatic tissues (ANPTs), but not in PDAC with perineural invasion. Meanwhile, we found that neutrophil-like MDSCs (nMDSCs), but not monocyte-like MDSCs (mMDSCs), were significantly increased in PBMCs and tumor tissues of PDAC patients. Further observation identified two distinct subsets of nMDSCs, CD13 hi and CD13 low nMDSCs in PDAC patients, which have not been reported previously. Despite a similar morphology, CD13 hi nMDSCs expressed higher levels of CD11b, CD33, CD16 and arginase 1 but lower levels of CD66b than CD13 low nMDSCs. Importantly, CD13 hi MDSCs, compared with CD13 low nMDSCs, more effectively suppressed alloreactive T cell responses via an arginase-1-related mechanism. After tumor resection, the circulating CD13 hi nMDSCs were decreased markedly. PDAC patients with more CD13 hi nMDSCs had a shorter overall survival than those with less CD13 hi nMDSCs. To conclude, we identified two novel MDSC subsets with different characteristics and functions in PDAC, demonstrated the association of the two MDSC subsets with cancer progression, and explored their roles in perineural invasion and immune escape of PDAC.